Spillage of bacterial products during colon surgery increases the risk of liver metastases development in a rat colon carcinoma model. (2nd September 2018) - Grewal, Simran; Korthouwer, Rianne; Bögels, Marijn; Braster, Rens; Heemskerk, Niels; Budding, Andries E.; Pouw, Stephan M.; van Horssen, Jack; Ankersmit, Marjolein; Meijerink, Jeroen; van den Tol, Petrousjka; Oosterling, Steven; et al.
ABSTRACT: Surgical resection of the primary tumor provides the best chance of cure for patients with colorectal carcinoma (CRC). However, bacterial translocation during intestinal surgery has been correlated with poor long-term oncological outcome. Therefore, we investigated the influence of bacterial contamination during colon surgery on CRC liver metastases development. Blood and liver samples of patients undergoing resection of primary CRC or liver metastases were collected. Cell numbers, activation markers and inflammatory mediators were determined. Tumor cell adhesion and outgrowth after sham- or colectomy operations were determined in a rat model, in which tumor cells had been injected into the portal vein. White blood cells and granulocytes were increased in per- and post-operative patient blood samples. IL-6 was also increased post-operatively compared to the preoperative level. Expression of NOX-2, NOX-4 and polymorphonuclear cells (PMNs) numbers were elevated in post-operative human liver samples. In vitro stimulation of macrophages with plasma of rats after colectomy resulted in production of reactive oxygen species (ROS). Colectomy in rats increased D-lactate levels in plasma, supporting bacterial translocation. Decreased expression of tight junction molecules and increased tumor cell adhesion and outgrowth was observed. Treatment with a selective decontamination of the digestive tract (SDD) cocktail decreased tumor cell adherence after colectomy. In conclusion, postoperative bacterial translocation may activate liver macrophages and PMNs, resulting in ROS production. As we previously showed that ROS release led to liver vasculature damage, circulating tumor cells may adhere to exposed extracellular matrix and grow out into liver metastases. This knowledge is pivotal for development of therapeutic strategies to prevent surgery-induced liver metastases development.